2020
DOI: 10.3390/agronomy10101599
|View full text |Cite
|
Sign up to set email alerts
|

Can Control of Glyphosate Susceptible and Resistant Conyza sumatrensis Populations Be Dependent on the Herbicide Formulation or Adjuvants?

Abstract: In this work, we studied the effect of three glyphosate formulations (isopropylamine, ammonium and potassium salts) and two non-ionic adjuvants on the resistance response of two resistant (R1, R2) and one susceptible population of the highly invasive Asteraceae, Conyza sumatrensis, from Southern France vineyards. Only in R1, an amino acid substitution (Pro106Thr) was found in the enzyme 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS). The two adjuvants, in a similar fashion, significantly reduced GR50 valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(71 reference statements)
1
6
0
Order By: Relevance
“…Still, drift does not reach the target site and shows poor efficacy against disease management [ 132 ]. However, nowadays, to improve the effectiveness of pesticides applications, the delivery mechanism has been upgraded via adding surfactants, nano-based formulations, and improved spraying technology [ 133 , 134 ]. In general, during pesticide application, surfactants have been used as an additive or adjuvants and mixed with pesticides that help in dispersion, emulsification, better spreading, or increasing the contact area with the plant surface, which enables the pesticides to better reach the target pests or target organisms [ 135 ] ( Figure 4 ).…”
Section: Biosurfactant Application In Plant Disease Managementmentioning
confidence: 99%
“…Still, drift does not reach the target site and shows poor efficacy against disease management [ 132 ]. However, nowadays, to improve the effectiveness of pesticides applications, the delivery mechanism has been upgraded via adding surfactants, nano-based formulations, and improved spraying technology [ 133 , 134 ]. In general, during pesticide application, surfactants have been used as an additive or adjuvants and mixed with pesticides that help in dispersion, emulsification, better spreading, or increasing the contact area with the plant surface, which enables the pesticides to better reach the target pests or target organisms [ 135 ] ( Figure 4 ).…”
Section: Biosurfactant Application In Plant Disease Managementmentioning
confidence: 99%
“…The same authors suggested that the combination of plant extracts with reduced rates of herbicides is a cost-effective approach for weed management in wheat. Similarly, the integration of adjuvants into herbicide tank mixtures is a promising method to reduce herbicide input or increase herbicide efficacy and achieve high levels of weed control, something quite desirable against herbicide-resistant weeds [103]. The formulation of some active ingredients, such as glyphosate, should be also considered to avoid spraying failures [104].…”
Section: Non-chemical Tools As Promising Alternatives To Herbicidesmentioning
confidence: 99%
“…96 For systemic herbicides, such as glyphosate, the herbicide resistance tests include analysis of the biokinetics in the whole plant. 97,98 An analytical review with technologies up to 2013 gathers all relevant knowledge on the available tests and methods for confirmation of herbicide resistance. 99 In Table 4, several recent onfarm, portable, and rapid diagnostic tests for herbicide resistance reported after 2013 are presented in detail to assist the screening of IPS for putative herbicide resistance.…”
Section: Early Weed Detection and Herbicide Resistance Screening Tool...mentioning
confidence: 99%